2016
DOI: 10.1007/s10439-016-1669-4
|View full text |Cite
|
Sign up to set email alerts
|

CareToy: Stimulation and Assessment of Preterm Infant’s Activity Using a Novel Sensorized System

Abstract: Early intervention programs aim at improving cognitive and motor outcomes of preterm infants. Intensive custom-tailored training activities are usually accompanied by assessment procedures, which have shortcomings, such as subjectivity, complex setups, and need for structured environments. A novel sensorized system, called CareToy, was designed to provide stimulation in the form of goal-directed activity training scenarios and motor pattern assessment of main developmental milestones, such as rolling activity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
(39 reference statements)
0
14
0
1
Order By: Relevance
“…A previous pilot study confirmed both feasibility of the CareToy System as a tool in promoting EI in infants and validity of study design [1617]. This Randomized Clinical Trial (RCT) study was aimed at testing short-term effects of CareToy training on motor and visual development in 3–9 month old preterm infants.…”
Section: Introductionmentioning
confidence: 80%
“…A previous pilot study confirmed both feasibility of the CareToy System as a tool in promoting EI in infants and validity of study design [1617]. This Randomized Clinical Trial (RCT) study was aimed at testing short-term effects of CareToy training on motor and visual development in 3–9 month old preterm infants.…”
Section: Introductionmentioning
confidence: 80%
“…It has been suggested that subjects with motor disorders could benefit from IMUs for the following three purposes: (1) Objective quantification of motor disorders; (2) Proprioceptive enhancement through visual-motor feedback; (3) Functional compensation via an inertial person-machine interface [29]. From a clinical assessment point of view for CP, IMUs have been successfully applied for the stimulation and analysis of activity using interactive games [67], for the assessment of lower limb spasticity [58], during gait [30], and for the assessment of specific characteristics in the cervical spine in small samples [11,68]. Following the increasing interest and evidence of the benefits of IMU application in pathological populations, in terms of guiding clinical decision making (e.g., quantify deficits and determine progress in time) [69], the current study adds the assessment of cervical ROM to the field of research of IMU in CP.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have made this family-centered approach clear in the title or program name 5,10,11 and others brought some principles of this approach to the methodology, when it was noticeable that the family was an important point of the intervention that was evaluated 14,16,17,20,22 . Few studies did not mention the family as a participant of the intervention 12,13,18 .…”
Section: Resultsmentioning
confidence: 99%